2021
DOI: 10.1029/2020jc016738
|View full text |Cite
|
Sign up to set email alerts
|

Estuarine Circulation, Mixing, and Residence Times in the Salish Sea

Abstract: The exchange flow is widely recognized as a defining property of tidally averaged estuarine circulation. The persistent inflow of deep, salty water and outflow of shallow, somewhat fresher water is often many times greater in volume flux than all the rivers entering a system. As a result, the exchange flow controls residence times and biogeochemical gradients. Physically this circulation is a result of the density contrast between ocean and river water, combined with mixing and advection from tidal currents (G… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 59 publications
1
52
1
Order By: Relevance
“…Sustained warming of Salish Sea waters was due to the combined effect of higher atmospheric heat flux (+ 19% relative to reference 45.2 W/m 2 ) and conveyance of warmer waters from the shelf via strong estuarine exchange flow into the Salish Sea. The magnitude of the estuarine flow is estimated in the range of 100-150 × 10 5 m 3 /s (Sutherland et al, 2011;Khangaonkar et al, 2017Khangaonkar et al, , 2018Olson et al, 2020), MacCready et al, 2021). It is a function of mean water depth (∝ H 3 ) and depth-averaged density (salinity) gradient (∝ ∂ S ∂X ) as presented analytically by Hansen and Rattray (1965), Dyer (1973), andMacCready (2004), MacCready (2007) for partially mixed estuaries, by Rattray (1967) for fjords, and by Khangaonkar et al (2011) for Salish Sea subbasins.…”
Section: Resultsmentioning
confidence: 99%
“…Sustained warming of Salish Sea waters was due to the combined effect of higher atmospheric heat flux (+ 19% relative to reference 45.2 W/m 2 ) and conveyance of warmer waters from the shelf via strong estuarine exchange flow into the Salish Sea. The magnitude of the estuarine flow is estimated in the range of 100-150 × 10 5 m 3 /s (Sutherland et al, 2011;Khangaonkar et al, 2017Khangaonkar et al, , 2018Olson et al, 2020), MacCready et al, 2021). It is a function of mean water depth (∝ H 3 ) and depth-averaged density (salinity) gradient (∝ ∂ S ∂X ) as presented analytically by Hansen and Rattray (1965), Dyer (1973), andMacCready (2004), MacCready (2007) for partially mixed estuaries, by Rattray (1967) for fjords, and by Khangaonkar et al (2011) for Salish Sea subbasins.…”
Section: Resultsmentioning
confidence: 99%
“…Situated in a temperate rainforest and composed of deep fjords and large glacial‐fed estuaries, the oceanography of the Salish Sea is distinct from many of the other regions represented in our global temperate literature search. The estuarine environment is unusual for kelp, with periodic or seasonal changes in salinity, temperature, turbidity, and other water column parameters that are often much larger than observed in open coast environments where most kelps are found (MacCready et al, 2021 ). Research has shown that kelps can exhibit population‐level differences in response to environmental stress (Buschmann et al, 2004 ; Flukes et al, 2015 ; Hollarsmith et al, 2020 ; King et al, 2019 ), and recent population genetic work on bull kelp in the Salish Sea revealed distinct genetic clusters that aligned with oceanographic currents, geographic and benthic features, and environmental variables (Gierke, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, these views of the circulation are often qualitative since speeds are not well known, and in certain cases a geostrophically controlled circulation could be directed along isopleths rather than across them. Quantitative tracer-based approaches include the ''box-model''-based Knudsen relations for estuarine flow (Hansen and Rattray 1965;MacCready et al 2018) or more complex variations thereof, applied locally by Pawlowicz (2001), Pawlowicz (2014), andMacCready et al (2021); or optimal water mass analyses (Tomczak 1981)-this latter approach was previously used along the thalweg of the Salish Sea as a whole by Masson (2006).…”
Section: Introductionmentioning
confidence: 99%
“…properties-which can be separated from the mean flux via a Reynolds decomposition and termed ''eddy flux'' (Davis 1991)-depends on details of the time-varying current field, and is important to the transport of tracers in energetic regions of the ocean (Wunsch 1999). Numerical investigations have been attempted for the Salish Sea circulation on a number of occasions, but have generally concentrated on circulation aspects closer to the Pacific entrance (Marinone and Pond 1996;Masson and Cummins 2004;MacCready et al 2021).…”
Section: Introductionmentioning
confidence: 99%